PENGARUH PENGGUNAAN GAWAI PADA REMAJA AWAL DENGAN KELEKATANNYA PADA ORANG TUA - Amita Diananda; Reno Intan (stit-islamic-village, 2021)
Gadget usage among early adolescent is increasing rapidly in the last decade. Adolescent today, were born when gadget is already here and it becomes part of their daily life. Eventhough peer and school environment become more influencing in adolescent, but parent role is still important. The purpose of this study is to see gadget usage among adolescent in their daily life, and to find out how it affects the attachment to their parent. The Inventory of Parent and Peer Attachment (IPPA Revision) is used to assessed the attachment between adolescent to their parent and peer (n=115). The result shows that gadget usage among early adolescent, gives an effect to the attachment between early adolescent and parent. It is suggested to do more investigation such as doing interview and observation for the next research in order to get more information regarding what is the effect of this attachment style to early adolescent well-being.